Learning stimulated by clinical cases – experience with the use of active methodology in the discipline of allergy and clinical immunology during the COVID-19 pandemic - de Almeida, Nícolas Apratto; Lima, Juliana Louise Dias; Moreira, Iramirton Figuerêdo (Seven Editora, 2023)
In March 2020, the Director-General of the World Health Organization declared a state pandemic due to the spread of COVID-19. As a result, all educational institutions in Brazil were forced to interrupt face-to-face classes, which has led to the multiplication of virtual education environments, according to Silva et al. (2020).DOI: https://doi.org/10.56238/devopinterscie-083